Striatum-related spontaneous coactivation patterns predict treatment response on positive symptoms of drug-naive first-episode schizophrenia with risperidone monotherapy - Zong, Xiaofen; Wu, Kai; Li, Lei; Zhang, Jiangbo; Ma, Simeng; Kang, Lijun; Zhang, Nan; Lv, Luxian; Sang, Deen; Weng, Shenhong; Chen, Huafu; Zheng, Junjie; et al. (Frontiers in Psychiatry, 2023)
Background: Evidence from functional magnetic resonance imaging (fMRI) studies of schizophrenia suggested that inter-individual variation in stationary striatal functional circuit may correlate with antipsychotic treatment response. However, little is known about the role of dynamic striatum-related network in predicting patients’ clinical improvement. Spontaneous coactivation patterns (CAPs) technique has recently been a vital step forward in uncovering the nonstationary nature of functional brain networks. Methods: Forty-two drug-naive first-episode schizophrenia patients were scanned by fMRI and T1W before and after 8-week risperidone monotherapy. The striatum was divided into 3 subregions including putamen, pallidum and caudate. The spontaneous CAPs and CAP states were utilized to measure the dynamic characteristics of brain networks. We used DPARSF and Dynamic Brain Connectome software to analyze each subregion-related CAPs and CAP states for each group, and then compared the between-group differences of the neural network biomarkers. We used the Pearson’s correlation analysis to compute the associations between the neuroimaging measurements with between-group differences and the improvement of patients’ psychopathological symptoms. Results: In the putamen-related CAPs, patients showed significantly increased intensity in the bilateral thalamus, bilateral supplementary motor areas, bilateral medial and paracingulate gyrus, left paracentral lobule, left medial superior frontal gyrus, and left anterior cingulate gyrus compared with healthy controls. After treatment, thalamic signals in the putamen-related CAP 1 showed significant increase, while the signals of the medial and paracingulate gyrus in the putamen-related CAP 3 revealed significant decrease. The increase of thalamic signal intensity in the putamen-related CAP 1 demonstrated significantly positive correlations with the percentage reduction of PANSS_P. Conclusion: This study for the first time combines striatal CAPs and fMRI to explore treatment response-related biomarkers in the early phase of schizophrenia. Our findings suggest that dynamic changes of CAP states in the putamen-thalamus circuit may be potential biomarkers for predicting patients’ variation in short-term treatment response of positive symptoms.